Never work harder than your students & other principles of great teaching - Jackson, Robyn Renee (Alexandria, VA : Association for Supervision and Curriculum Development, 2009)
Discusses ways to develop a mindset by applying seven core principles to one's pedagogical technique until they become automatic, including understanding of the students' educational background and path, support, feedback, quality over quantity, and not working harder than one's pupils.
Start where your students are -- Know where your students are going -- Expect to get your students there -- Support your students -- Use effective feedback -- Focus on quality, not quantity -- Never work harder than your students -- Putting it all together tools.
Includes bibliographical references (p. 240-241) and index.
Professional
Keywords: Effective teaching; Teacher effectiveness; Effective teaching; Teacher effectiveness